2022
DOI: 10.1371/journal.pone.0274812
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors were more important than perceived risk or optimism for compliance to infection control measures in the early stage of the COVID-19 pandemic

Abstract: Compliance to infection control measures may be influenced both by the fear of negative consequences of a pandemic, but also by the expectation to be able to handle the pandemic’s challenges. We performed a survey on a representative sample for Norway (N = 4,083) in the first weeks of the COVID-19 lock-down in March 2020. We had preregistered hypotheses to test the effect of optimism and perceived risk on compliance. Perceived risk had small effects on increasing compliance and on leading to more careful infor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
2
1
0
Order By: Relevance
“…Under the theme of "Being responsible", the secondorder construct of "Caring for others" were mentioned by several participants. This finding may correspond to a Norwegian cross-sectional survey that found that believing the infection control measures could protect others was an important determinant for following the measures (Saetrevik & Bjørkheim, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…Under the theme of "Being responsible", the secondorder construct of "Caring for others" were mentioned by several participants. This finding may correspond to a Norwegian cross-sectional survey that found that believing the infection control measures could protect others was an important determinant for following the measures (Saetrevik & Bjørkheim, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…All three samples reported that they had seen themselves to be less at risk for infection and disease than for those close to them and for the population in general. This indicates a previously observed phenomenon sometimes referred to as "optimism bias" (Saetrevik & Bjørkheim, 2022;Sharot, 2011).…”
Section: Psychological Mechanisms For Risksupporting
confidence: 69%
“…In a pandemic setting, this may lead to seeing the likelihood of being infected as lower for oneself than for others, or expecting to have milder symptoms that others if one is infected. Studies on the COVID-19 pandemic have shown that people tend to ascribe a higher risk for others compared to themselves (Pascual-Leone et al, 2021;Saetrevik & Bjørkheim, 2022;Salgado & Berntsen, 2021).…”
Section: Everyday Decision-making In the Earlymentioning
confidence: 99%